(untitled) (Bangladesh Journal of Pharmacology, 2015)
The present study was done to determine whether kaempferol, a natural polyphenol of the flavonoid family, affects Epithelial-Mesenchymal Transition (EMT) in non-small cell lung cancer cells. Kaempferol not only inhibited cancer cell proliferation and migration in a dose-dependent manner but also modulated the expression of EMT-related proteins E-cadherin and vimentin which are indispensible to cellular motility, invasiveness and metastasis. These results indicate that kaempferol suppresses non-small cell lung cancer migration by modulating the expression of EMT proteins. Therefore, kaempferol may be useful as a potential anticancer agent for non-small cell lung cancer.